POST-COVID-19 COGNITIVE IMPAIRMENT AS A NEUROPSYCHIATRIC SYNDROME: A REVIEW OF MECHANISMS, CLINICAL FEATURES, AND IMPACT ON QUALITY OF LIFE - Natalia Żelichowska; Aleksandra Grotkowska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Post-COVID-19 Condition (PCC), commonly referred to as long COVID, has become a major post-pandemic health issue, with many individuals experiencing persistent cognitive and neuropsychiatric symptoms. These difficulties, often described as “brain fog”, include problems with memory, executive functioning and processing speed, and can markedly disrupt daily life, emotional well-being and work capacity.Methods: A narrative review was performed using PubMed and Google Scholar. Keywords included “post-COVID cognitive impairment”, “long COVID”, “neurocognitive dysfunction”, and related terms. Original studies, cohort research, systematic reviews and meta-analyses were screened for relevance. Documents from WHO, NICE were also reviewed to supplement diagnostic definitions.Results: Current studies consistently indicate that cognitive impairment represents one of the most common manifestations of long COVID, with estimates ranging from 20% to 30%. Difficulties with executive function, memory, sustained attention and information-processing speed form the core pattern of impairment and exert a meaningful impact on daily independence and well-being. Neuroimaging findings support these complaints, showing corresponding metabolic, structural and microvascular changes. Proposed mechanisms most often involve sustained neuroinflammation, immune imbalance, endothelial injury and microvascular dysfunction.Conclusions: Post-COVID cognitive impairment remains a significant clinical challenge, affecting daily functioning and long-term recovery for many patients. Clearer diagnostic criteria and improved assessment tools integrating neuropsychological testing, imaging and biomarker data are needed to enhance recognition and to identify those at higher risk. Ongoing research into therapeutic strategies remains essential for optimising long-term management and outcomes in affected patients.